Engineered nanomaterials in plant protection: their controlled, site-directed delivery and phytotoxicity - Patil, Vinod W.; Suryawanshi, Nilkanth S.; Bokhad, Mohanish N.; Parsodkar, Vanashree J.; Narhe, Asha S. (Current Botany, 2024)
Engineered nanomaterials (ENMs) are being produced and utilized in certain nanoformulations almost in every sector of development including agriculture. The diverse groups of engineered nanoparticles (ENPs) provide numerous benefits in agriculture, but their bulk and direct delivery pose a serious risk to the plants and ecosystem for a long time. The harmful effects on all the exposed living systems are owing to the variable shape, size, behaviour and toxic properties of ENPs. The accumulated ENMs in plant tissue may lead to biomagnification at a higher trophic level causing severe toxicity. The hazardous effects of these entities can be minimized with their controlled, specified and targeted delivery to the crop plants. Such smart-delivery systems as Ehrlich’s ‘magic bullets’ are being demonstrated for nutrients and growth enhancers, fertilizers, pesticides and weedicides; as well as biomolecules in plant genetic engineering. This review summarizes the benefits of ENMs and ENPs in plant protection to increase crop productivity, their targeted delivery suggesting sustainable utilization, and the available information on phytotoxicity.